Differential diagnosis of dermatophytosis. - Gelmetti, C. (European Journal of Pediatric Dermatology, 2001)
The differential diagnosis of tinea corporis is practically endless, due to the enormous variety of responsible fungal species and the extreme polymorphism of the clinical features. Psoriasis, pityriasis rosea and nummular eczema should be more frequently differentiated from tinea corporis, whereas psoriasis, erythrasma and contact dermatitis from tinea inguinalis and, finally, dyshidrosis and contact dermatitis from tinea pedis. Less frequently, the differential diagnosis from impetigo, mycosis fungoides, discoid lupus erythematosus and secondary syphilis should be considered. Moreover, the diagnosis is more difficult in Negro subjects, due to the lack or scarce evidence of erythema. Finally, “tinea incognito” should be mentioned. This term applies to those skin mycoses presenting with symptoms and signs other than expected. The most frequent cause of “tinea incognito” is topical corticosteroid treatment, prescribed as a consequence of a diagnostic mistake.